HAMBATAN LULUSAN NERS DALAM MENGHADAPI UJI KOMPETENSI NERS INDONESIA - Kholifah, Siti; Kusumawati, Wiwik (The Indonesian Journal of Health Science, 2016)
Background: Identifying the barriers faced by graduate nurses become one of the efforts of educational institutions and graduate nurses to evaluate the results of the low passing rate on Indonesian Nurses Competency Test (INCT). This study aims to analyze barriers of graduated nurses from Faculty of Health Sciences, University of Muhammadiyah Jember to face INCT.  Methods: The method used is descriptive method with qualitative approach that involves 6 people graduate nurses Faculty of Health Sciences, University of MuhammadiyahJember who did not pass INCT. Data obtained through focus group discussions and then analyzed by constant comparative method.  Results: The results showed that the barriers of graduated nurses in the face of INCT consists of theimproper execution time of INCT, unfocused learning process, confusion, anxiety, an inadequate knowledge of INCT, the hesitation in the answer, the computer screen?s brightness, and an error computers.  Conclusion: The results indicate that there are obstacles in the preparatory phase and during the implementation INCT that affect the success rate of graduate nurses in INCT.